(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the scientific-theoretical problems of discourse research within corpus linguistics, and examines the opinions of linguists about the advantages and disadvantages of research in this direction. The author’s opinion on the synergistic effect of the corpus and on the base of discourse aspects has been justified the effectiveness of discourse research within the framework of corpus linguistics.